Pengaruh Dual-Task Training Terhadap Keseimbangan Dinamis Pasien Gagal Ginjal Kronik Dengan Hemodialisis (Studi Quasi Eksperimental di RS Haji Jakarta) - Achwan, Achwan; Pambudi, Restu Arya (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
The quality of CKD is damage to the structure and function of the kidneys that lasts for more than 3 months with or without a decrease in the glomerular filtration rate and the damage develops progressively, causing a buildup of metabolic waste which results in disturbances in water, electrolyte and acid base balance [ 16]. According to the Global Burden of Disease study, it has been shown that CKD has emerged as a non-communicable disease which has become one of the main causes of death worldwide in the last 2 decades.[4] The prevalence of CKD continues to increase, in 2017 around 843.6 million people experienced it worldwide. The most common causes of CKD are hypertension (37%) and diabetes mellitus (27%).[8] Hemodialysis is the most widely used treatment but is unable to cure and compensate for the loss of metabolic or endocrine activity carried out by the kidneys and does not restore the quality of life of CKD patients. [14] Dual-Task Training is carried out by adding cognitive tasks to motor tasks so that attention will be divided to respond to stimuli and complete the two tasks simultaneously. [5] Addition of tasks is essential to reduce the risk of falls in patients. Almost all activities in daily life involve two tasks simultaneously. [1 The measuring tool in this study is the Timed Up and Go Test (TUGT) which aims to observe gait and predict the risk of falling. This test consists of how long it takes a person to stand up from a chair, walk 3 meters, turn around, and sit down again. The aim of this research is to determine the effect of Dual-Task Training on the Dynamic Balance of CKD Patients on Hemodialysis at Haji Hospital Jakarta in 2024. This research uses a quasi-experimental research design with a pre and post test two group design. Purposive sampling technique with predetermined inclusion and exclusion criteria. The number of samples in this study was 50 people. Data collection was carried out using TUGT and checklists for carrying out sample selection and interventions. Data analysis was carried out using univariate to determine the characteristics of the sample and bivariate to determine the effect of Dual-Task Training on Dynamic Balance. Bivariate analysis was preceded by a normality test with Shapiro Wilk and the data was found to be normally distributed so that the next test was carried out with the Paired T Test to determine the effect of Dual-Task Training. The final data analysis was using the Independent T test with the results of differences in influence between the treatment and control groups which concluded that there was a significant effect of Dual-Task Training in improving the dynamic balance of hemodialysis patients with kidney failure. The final stage is interpretation and conclusion.